Pengembangan Agribisnis Tanaman Hias di Era Digitalisasi dan Legalitasnya - Fani Budi Kartika; Fitri Yani; Tonna Balya; Muhsin Lambok Ilvira; Muhammad Ihsan; Stivani Ismawira Sinambela; Rika Fitri Ilvira (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to develop ornamental plant agribusiness in Bangun Sari Village, Tanjung Morawa District, North Sumatra, through the use of digital technology and increasing understanding of business legality. Bangun Sari Village has great potential in cultivating ornamental plants, but is still limited in terms of using technology for marketing and business management. Therefore, this activity involves training and workshops that focus on the use of social media and e-commerce platforms to expand market reach, as well as providing knowledge regarding the importance of business legality. The results of this activity show that the majority of participants succeeded in adopting digital technology to market their products more efficiently, increase their awareness of the importance of business legality, and expand their market network to outside the region and international markets. Thus, this activity not only improves digital skills, but also encourages significant social change, with agribusiness actors starting to see the potential of ornamental plant agribusiness as a professional and sustainable business. In the future, it is hoped that the application of digital technology in ornamental plant agribusiness will become more widespread, provide new economic opportunities for society, and support the sustainable growth of the agribusiness sector at the local and national levels.